2008
DOI: 10.1103/physrevb.78.045431
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the ratchet effect in a two-dimensional electron system with broken spatial inversion symmetry

Abstract: We report on experimental evidence of directed electron transport, induced by external linear-polarized microwave irradiation, in a two-dimensional spatially-periodic asymmetrical system called "ratchet". The broken spatial symmetry was introduced in a high mobility two-dimensional electron gas based on AlGaAs/GaAs heterojunction, by patterning an array of artificial semi-discs-shaped antidots. We show that the direction of the transport is efficiently changed by microwave polarization. The dependence of the e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
61
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 27 publications
8
61
0
Order By: Relevance
“…Quite generally, this can be achieved by breaking spatial mirror symmetry (see, e.g., Refs. [52][53][54]). Particle-hole symmetry need be broken as well, which is the basic requirement for any thermoelectric device.…”
Section: Introductionmentioning
confidence: 99%
“…Quite generally, this can be achieved by breaking spatial mirror symmetry (see, e.g., Refs. [52][53][54]). Particle-hole symmetry need be broken as well, which is the basic requirement for any thermoelectric device.…”
Section: Introductionmentioning
confidence: 99%
“…While research aimed to development of THz FET detectors is focused on single gate structures, recently several groups have shown that higher sensitivities are expected for structures with periodic symmetric and asymmetric metal stripes or gates. 9,[15][16][17][18][19][20][21][22] In particular, dual-grating-gate (DGG) FET are considered as a good candidate for sensitive THz detection. The first data obtained on dual-gated-structures demonstrated a substantial enhancement of the photoelectric response and an ability to control detector parameters by variation of individual gate bias voltage.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the Ratchet device has been proposed to be used in the fabrication of current generators and detectors at high microwave frequencies [2][3][4][5][6]; also with the possibility of using the terahertz radiation [9,10]. The concept of operation [2][3][4][5][6][7] consists of radiating a two-dimensional electron gas asymmetric system with a microwave linear polarized radiation and producing a DC induced photovoltage. At low temperature, this effect is recently observed in AlGaAs/GaAs [2,3] and Si/SiGe [4][5][6] heterostructure samples which are characterized by the high mobility of electrons.…”
Section: Introductionmentioning
confidence: 99%